2003
DOI: 10.1182/blood-2002-06-1688
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin specifically interferes with GM-CSF signaling in human dendritic cells, leading to apoptosis via increased p27KIP1 expression

Abstract: The longevity of dendritic cells (DCs) is a critical regulatory factor influencing the outcome of immune responses. Recently, we demonstrated that the immunosuppressive drug rapamycin (Rapa) specifically induces apoptosis in DCs but not in other myeloid cell types. The present study unraveled the mechanism used by Rapa to induce apoptosis in human monocyte-derived DCs. Our data demonstrate that granulocyte-macrophage colonystimulating factor (GM-CSF) preserves DC survival specifically via the phosphatidylinosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 52 publications
9
107
4
Order By: Relevance
“…Other reports describe p27 as antiapoptotic gene (St Croix et al, 1996;Eymin et al, 1999). Therefore, this suggests that the survival effects of p27 kip1 are cell-type specific and may be mediated by p27 effects on antiapoptotic protein expression (Eymin et al, 1999;Woltman et al, 2003). Whether similar molecular mechanisms underlie the increase in TRAIL resistance upon silencing of p27 kip1 remains to be further investigated.…”
Section: Discussionmentioning
confidence: 94%
“…Other reports describe p27 as antiapoptotic gene (St Croix et al, 1996;Eymin et al, 1999). Therefore, this suggests that the survival effects of p27 kip1 are cell-type specific and may be mediated by p27 effects on antiapoptotic protein expression (Eymin et al, 1999;Woltman et al, 2003). Whether similar molecular mechanisms underlie the increase in TRAIL resistance upon silencing of p27 kip1 remains to be further investigated.…”
Section: Discussionmentioning
confidence: 94%
“…In this context, Li et al 56 found a role for 4E-BP1 in the translational control of proteins critical for cell survival. We observed in this study the suppressed phosphorylation of 4E-BP1 by treatment of Ocl with rapamycin, which may account for part of the apoptotic 58 reported that GM-CSF-mediated survival of dendritic cells indeed depends on PI3K/mTOR signaling and MCL-1. These findings along with those presented here suggest a broader involvement of mTOR in cell survival within the monocyte/macrophage-derived cell lineages.…”
Section: Discussionmentioning
confidence: 53%
“…Monocyte-derived DCs (MD-DCs) were generated as described (22,23). Briefly, PBMC were separated by density gradient centrifugation from leukocyte concentrates obtained from healthy volunteers.…”
Section: Cell Culturementioning
confidence: 99%